Ocean Chlorophyll Feedback in a Coupled Ocean-Atmosphere Model for the Mediterranean and Black Seas - Karagiorgos, John; Vervatis, Vassilios; Sofianos, Sarantis (Journal of Geophysical Research: Oceans, 2025)
Abstract Ocean water clarity, influenced by marine chlorophyll concentration, significantly alters the distribution of shortwave radiation in the water column. This work aims to assess the effects of varying chlorophyll on the upper-ocean physical properties and their subsequent impact on the atmosphere, using a coupled ocean-atmosphere regional model for the Mediterranean and Black Seas. We performed 11-year (2011–2021) twin-simulation experiments based on different chlorophyll concentrations to estimate the penetration of solar radiation in the ocean. The first simulation used a monthly climatology field of chlorophyll concentrations derived from satellite observations, while in the second experiment, the chlorophyll concentration was kept constant at 0.05 mgm−3 \$mg\ {m}^{-3}\$, representing clear water conditions. Results show that radiative heating driven by chlorophyll amplifies the seasonal cycle of temperature in the upper layers, leading to increased surface warming in summer and surface cooling in winter. Also, higher surface chlorophyll contributes to cooling in subsurface layers throughout the year due to its shading effect. The temperature response to chlorophyll variations is controlled by the mixed layer depth and a balance between (a) direct near-surface radiative heating due to the chlorophyll absorption and (b) indirect cooling resulting from vertical turbulent mixing processes with subsurface waters. The atmosphere moderates the seasonal sea surface temperature (SST) response caused by chlorophyll differential heating primarily through changes in latent heat flux. Ultimately, our simulations suggest that increased surface chlorophyll concentrations enhance the Mediterranean overturning circulation, highlighting the necessity of incorporating realistic optical forcing into regional climate modeling studies.
Keywords: Mediterranean and Black Seas; NEMO-OASIS-WRF; ocean chlorophyll; ocean-atmosphere coupling